Design of Discharge Planning Application for Mental Health Disorders Patients in Android-Based Information System - Arief Nugroho; Blacius Dedi; Julvainda Eka Priya Utama (Jurnal Ilmu Keperawatan Jiwa, 2022)
Based on data there are an average of 18 patients per month readmission, they are re-treated on average after 12 days at home. It is complex management of health workers to handle it, especially the preparation of patient discharge. Design of Discharge Planning Application for Mental Health Disorders Patients In Android-Based Information System is in line with technological advances that facilitate the patient's learning process not only with leaflets and posters but also with multimedia interactive media. Draft of discharge planning model based on an android information system for mental health disorder patients at RSJD Dr. Amino Gondohutomo Hospital Central Java Province. Phenomenological qualitative research with an action research approach. Data collection techniques used are FGD (Focus Group Discussion) and Expert Workshops.  Seven themes are assessment and discharge planning from the admission. Patients, families, and patient responders at home. Important information that patients, families, and persons in charge must know. Basic needs, information, and education of patients while at home, professional group service plan. Empowerment of the patient's immediate environment from close family to health officials and agencies, monitoring, and evaluation are needed to ensure continuity of service.